Source rock potential of the Late Miocene Metochia formation of Gavdos Island, Greece - Pyliotis, I.; Zelilidis, A.; Pasadakis, N.; Panagopoulos, G.; Manoutsoglou, E. (Bulletin of the Geological Society of Greece, 2013)
Rock-Eval method was used to analyze 53 samples from late Miocene Metochia Formation of Gavdos Island (south of Crete Island) in order to characterize the contained organic matter and to evaluate its potential as source rock. The samples were collected from Metochia Section which consists of about 100 m thick marlssapropels alternations. Organic matter analysis showed that the studied succession could be subdivided into two parts. The lower one, which is generally rich in organic matter and the upper one, which is poor. In the lower part the rich horizons in organic matter are characterized by Kerogen type II, III and IV, with low oxygen content, and with fair to very good potential for gas and/or oil hydrocarbon generation. Additionally, the studied samples are thermally immature. Taking into account that the studied area has never been buried in such a depth to reach conditions of maturation, as well as, that the studied section in Gavdos is connected with Messara basin located in the northeastern and, finally, that the main part of Gavdos basin, which is situated between Gavdos and Crete islands, has continuously encountered subsidence, we could conclude that sediments of Metochia Formation could act as source rocks but in the more deep central part of the Gavdos basin.